1976
DOI: 10.1084/jem.143.3.684
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for direct linkage between antigen recognition and lytic expression in effector T cells.

Abstract: The mechanism of cytotoxicity mediated by thymus-derived (T) lymphocytes can be divided into two phases, one of antigen recognition, the other the cytolytic event. The antigen recognition phase shows immunological specificity and consists of the interaction of target cell antigen with the effector cell's antigen receptor site (1-3). The relationship between this accomodation and the subsequent killing process is unknown.Conceptually, one could view the role of the T cell's antigen receptor in one of two ways. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

1977
1977
1989
1989

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(11 citation statements)
references
References 6 publications
2
9
0
Order By: Relevance
“…This limited-release model is consistent with one-way killing of target CTLs by other (aggressor) CTLs, especially in an allogeneic MLC where the fraction of aggressor CTLs is not defined (30). At high aggressor/target ratios, several aggressor CTLs might be able simultaneously to adhere to and deliver their individually controlled release of toxic granules on a single hapless target CTL.…”
Section: Inhibition Of Granule-mediated Lysis Of Red Blood Cells By Csupporting
confidence: 53%
See 1 more Smart Citation
“…This limited-release model is consistent with one-way killing of target CTLs by other (aggressor) CTLs, especially in an allogeneic MLC where the fraction of aggressor CTLs is not defined (30). At high aggressor/target ratios, several aggressor CTLs might be able simultaneously to adhere to and deliver their individually controlled release of toxic granules on a single hapless target CTL.…”
Section: Inhibition Of Granule-mediated Lysis Of Red Blood Cells By Csupporting
confidence: 53%
“…The findings extend several other observations that CTLs make poor targets for other CTLs (12,27) . Yet many other studies have demonstrated that, under some circumstances, a CTL can be lysed when it is recognized by other CTLs (28)(29)(30), a phenomenon referred to as one-way killing …”
Section: Inhibition Of Granule-mediated Lysis Of Red Blood Cells By Cmentioning
confidence: 99%
“…Since LCM virus is not overtly cytopathic for lymphoid cells (4,5), direct killing of T cells by virus seems an unlikely explanation. One possible mechanism is based upon findings that one cytotoxic T cell can kill another (29)(30)(31), provided the former has receptors complementary for antigenic patterns on the latter (30). The presence of a high level of virus in the environment of responding cytotoxic T cells specific for LCM virus-induced antigenic patterns could result in cytotoxic cells or their precursors, becoming infected and displaying antigenic patterns complementary for their own antigen receptors.…”
Section: Discussionmentioning
confidence: 99%
“…$ Significantly greater lysis (P < 0.001) than with the relevant control of normal spleen cells on same target at the same effector:target ratio. § P < 0.01. specific cytotoxic T cells are themselves infected, display virus-induced antigen patterns complementary for their own antigen-receptors, and thus either commit suicide or kill each other (29)(30)(31). To test formally whether LCM virusinfected T cells are susceptible to T-cell-mediated lysis, spleen cells from LCM virus congenital carrier or from normal mice were stimulated in vitro with the T-cell mitogen Con A (32) for 5 days and then used as labeled target cells, either infected or uninfected, respectively.…”
Section: Suppression Of Primary Response In Vivo By Transfer Of Lcm Vmentioning
confidence: 99%
“…CTL, however, have to bind to their target through their antigen receptor to become efficient [23,24] and it is possible that this signal of activation, or a posterior event like the modification of cyclic nucleo tide levels or the delivery of the lethal hit share a SDIF-sensitive process with the mitotic cycle. It is in teresting to note along this line that quercetin, a sub stance related to disodium cromoglycate [25], and some monoclonal antibodies [reviewed in ref.…”
Section: Discussionmentioning
confidence: 99%